2019
DOI: 10.1136/gutjnl-2018-317601
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3B interaction with PRC2 modulates microenvironment to promote HCC progression

Abstract: ObjectiveAPOBEC3B (A3B), a cytidine deaminase acting as a contributor to the APOBEC mutation pattern in many kinds of tumours, is upregulated in patients with hepatocellular carcinoma (HCC). However, APOBEC mutation patterns are absent in HCC. The mechanism of how A3B affects HCC progression remains elusive.DesignA3B ­promoter luciferase reporter and other techniques were applied to elucidate mechanisms of A3B upregulation in HCC. A3B overexpression and knockdown cell models, immunocompetent and immune-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Most cancer types with a low proportion of nonmutagenic isoforms, specifically of A3B3, also had a higher rate of APOBEC-mediated mutation 150 burden 7,8 , with exceptions for tumors of KICH and LICH, in which APOBEC-signature mutations were negligible ( Figure S4). In these cancers, A3B might play a mitogenic rather than a mutagenic role as has been shown for hepatocellular carcinoma 29 and suggested for breast cancer 30 .…”
Section: The Ratio Of the Non-mutagenic Isoform A3b3 Is Higher In Normentioning
confidence: 79%
“…Most cancer types with a low proportion of nonmutagenic isoforms, specifically of A3B3, also had a higher rate of APOBEC-mediated mutation 150 burden 7,8 , with exceptions for tumors of KICH and LICH, in which APOBEC-signature mutations were negligible ( Figure S4). In these cancers, A3B might play a mitogenic rather than a mutagenic role as has been shown for hepatocellular carcinoma 29 and suggested for breast cancer 30 .…”
Section: The Ratio Of the Non-mutagenic Isoform A3b3 Is Higher In Normentioning
confidence: 79%
“…65 Recently, we reported that the epigenetic modifications in cancer cells may facilitate massive trafficking of MDSCs and TAMs to the TME by regulating the release of CCL-2, leading to high expression of PD-1 on tumor-infiltrating CD8 + T cells and tumor progression. 66 In addition, some other soluble mediators are involved in the immune cell trafficking. Our latest work has uncovered a new mechanism by which depression-induced neuropeptide Y (NPY) secretion activates the IL-6-STAT3 signaling pathway and TAM infiltration.…”
Section: Immunosuppressive Cellsmentioning
confidence: 99%
“…Recruitment of the aforementioned immunosuppressive MDSCs, TAMs, and T reg cells to the TME is largely driven by the secretion pattern of chemokines, including CCL2, CCL5, CCL7, CXCL1, and CXCL12, and their interaction with the corresponding receptors 65 . Recently, we reported that the epigenetic modifications in cancer cells may facilitate massive trafficking of MDSCs and TAMs to the TME by regulating the release of CCL‐2, leading to high expression of PD‐1 on tumor‐infiltrating CD8 + T cells and tumor progression 66 . In addition, some other soluble mediators are involved in the immune cell trafficking.…”
Section: Development Of T‐cell Exhaustionmentioning
confidence: 99%
“…In a recent study, Wang et al [8] revealed another important role of APOBEC3B in the cancer evolutionary process of mutation-selection-adaptation. Their study suggests that APOBEC3B can also contribute to the "selection" and "adaption" of malignant cells via facilitating the immune escape in a deaminaseindependent way.…”
mentioning
confidence: 99%